2014
DOI: 10.11646/zootaxa.3832.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the marine and estuarine fishes of Madang District, <br />Papua New Guinea, western Pacific Ocean, with 820 new records

Abstract: A checklist of the marine and estuarine fishes of Madang District is presented, combining both previous and new records. After the recent PAPUA NIUGINI 2012 expedition, a total of 1337 species in 129 families have been recorded from the region. One species and one family is not native (Cichlidae: Oreochromis mossambicus), but has been introduced. The native fish fauna of Madang therefore consists of 1336 species in 128 families. The largest families are the Gobiidae, Labridae, Pomacentridae, Apogonidae, Serran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
1
22
0
2
Order By: Relevance
“…Thrissina encrasicholoides has been recorded from Sri Lanka, south-eastern India (Vishakhapatnam), Andaman Islands, Indonesia, Papua New Guinea (Madang District), the Philippines and Queensland, Australia (Nelson 1981, Whitehead et al 1988, Krishnan and Mishra 1994, Wongratana et al 1999, Fricke et al 2014. It is newly reported here from southwestern Taiwan.…”
Section: Distributionmentioning
confidence: 58%
See 1 more Smart Citation
“…Thrissina encrasicholoides has been recorded from Sri Lanka, south-eastern India (Vishakhapatnam), Andaman Islands, Indonesia, Papua New Guinea (Madang District), the Philippines and Queensland, Australia (Nelson 1981, Whitehead et al 1988, Krishnan and Mishra 1994, Wongratana et al 1999, Fricke et al 2014. It is newly reported here from southwestern Taiwan.…”
Section: Distributionmentioning
confidence: 58%
“…Nelson (1983) also regarded Engraulis duodecim, described by Cope (1867) from a specimen supposedly collected from Beasley's Point, New Jersey, USA, as a junior synonym of T. encrasicholoides, pointing out the erroneous collection locality. Thereafter, Krishnan and Mishra (1994) reported the species from the Andaman Islands (specimens deposited in the Marine Biological Station, Zoological Survey of India, Madras) and Fricke et al (2014) reported a specimen (AMS I.16747-004) collected from Madang District, Papua New Guinea. Because there appear to be no further significant distribution records of T. encrasicholoides, the presently described specimens from south-western Taiwan are considered to represent the first record of the species from Taiwan and the northernmost records of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution. Pterocaesio tessellata is currently known from the eastern Indian to the western Pacific oceans, westward to Sri Lanka, eastward to Vanuatu, and north to the Philippines (Carpenter 1987, 2001, Allen and Erdmann 2012, Tatsukawa 2017, and now from southwestern Taiwan (presently reported study).…”
Section: Resultsmentioning
confidence: 83%
“…66, fig. A;Carpenter 2000: 618;Carpenter 2001Carpenter : 2939Allen and Adrim 2003: 39;Peristiwady et al 2003: 92;Adrim et al 2004: 121;Iwatsuki 2009: 147, unnumbered fig. ;Allen and Erdmann 2012: 466, unnumbered fig.…”
Section: Resultsunclassified
“…The latter location is in close proximity to deep oceanic waters, which also applies to the adjacent coast of eastern Papua New Guinea. For the latter, however, U. taeniopterus has not yet been reported (e.g., Fricke et al 2014).…”
Section: Discussionmentioning
confidence: 99%